O deslocamento espacial de imigrantes haitianos: da desterritorialização à reterritorialização - Ednaldo Tartaglia Santos; Odete Burgeile (Confins)
This research came from the interest in studying the presence of Haitian immigrants in Porto Velho, Rondonia, southern Brazilian Amazon. Our research question was the following: how is the migration process of a group of Haitian immigrants in Porto Velho, considering their spatial displacement inserted in a post-modern world? In order to answer this question, we made a qualitative ethnographic research and we inter-related it mainly to prospects on territory (GUATTARI; ROLNIK, 1996; HAESBAERT, 2012), about deterritorialization, reterritorialization and dereterritorialization (DELEUZE; GUATTARI, 1996, 1997; GUATTARI; ROLNIK, 1996; HAESBAERT, 2012). The data collected provided a historical and sociocultural study of Haitian immigrants involved in the dynamics of deterritorialization and reterritorialization motivated by the searching of work and better living conditions.